Monitoring and Internet connectivity system for small farms in remote and hard to reach regions - Petrov, Georgi; Kadrev, Vasil (Yearbook Telecommunications, 2019)
The purpose of this publication is to present the existing telecommunication connectivity problems of small and medium-sized farmers located in remote and hard to reach mountainous regions. The results relate to the development of an open hardware and software system for automated monitoring and determination of local meteorological forecasts for use by small and medium-sized farmers located in remote and hard to reach mountain regions. The contributions of this work are the in-depth analysis and the recommendations developed on the basis of this analysis. The developed system is part of a project concerning the construction and development of free internet access and monitoring systems in remote farms and in the mountainous regions of the country.